Problems of Identification and Analysis of Transaction Costs at the Economic Entity Level - Herasymenko Tetiana V. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The article is aimed at identifying and analyzing transaction costs when making management decisions at the level of an economic entity. In the course of the research, the following methods were used: grouping – in determining the main forms of transaction costs based on existing classifications; generalization – when systematizing information on the identification of approaches to the assessment and measurement of transaction costs; structural and logical – to determine the place of transaction costs in the structure of the enterprise’s costs; analysis and synthesis – to substantiate the recommendations for displaying information on the level of transaction costs at the enterprise in financial statements. The main forms of transaction costs on the basis of existing classifications are researched. Information on identification of approaches to valuation and measurement of transaction costs is systematized. The place of transaction costs in the structure of the enterprise’s expenses is determined. Recommendations on displaying information on transaction costs at the enterprise in the financial statements on the basis of their occurrence in a certain sphere of activity of the market entity (transaction costs of operational, financial, investment activities) are substantiated, which represents the scientific novelty of the research. It is concluded that the institutional approach, in particular application of the theory of transaction costs before their valuation and preparation of financial statements, allows not only identifying possible solutions to existing problems in accounting theory and practice, but also seting fundamentally new tasks that require non-standard solutions. The practical significance of the obtained research results is to determine the impact of transaction costs on the efficiency of the functioning of market entities and substantiate recommendations for displaying information about their level at the enterprise in financial statements.